Clinical Efficacy Protocol of Yinhuapinggan Granules: A Randomized, Double-Blind, Parallel, and Controlled Clinical Trial Program for the Intervention of Community-Acquired Drug-Resistant Bacterial Pneumonia as a Complementary Therapy - Wang, Jiaoli; Hu, Haoran; Du, Haixia; Luo, Man; Cao, Yilan; Xu, Jiaping; Chen, Tianhang; Guo, Yilei; Li, Qixiang; Chen, Wen; Zhang, Yifei; Han, Jin; et al. (Frontiers in Pharmacology, 2022)
Background Community-acquired bacterial pneumonia (CABP) is an important health care concern in the worldwide, and is associated with significant morbidity, mortality, and health care expenditure. Streptococcus pneumoniae is the most frequent causative pathogen of CABP. Common treatment for hospitalized patients with CABP is empiric antibiotic therapy using β-lactams in combination with macrolides, respiratory fluoroquinolones, or tetracyclines. However, overuse of antibiotics has led to an increased incidence of drug-resistant S. pneumoniae, exacerbating the development of community-acquired drug-resistant bacterial pneumonia (CDBP) and providing a challenge for physicians to choose empirical antimicrobial therapy. Methods Traditional Chinese medicine (TCM) is widely used as a complementary treatment for CDBP. Yinhuapinggan granules (YHPG) is widely used in the adjuvant treatment of CDBP. Experimental studies and small sample clinical trials have shown that YHPG can effectively reduce the symptoms of CDBP. However, there is a lack of high-quality clinical evidence for the role of YHPG as a complementary drug in the treatment of CDBP. Here, we designed a randomized, double-blind, placebo-controlled clinical trial to explore the efficacy and safety of YHPG. A total of 240 participants will be randomly assigned to the YHPG or placebo group in a 1:1 ratio. YHPG and placebo will be added to standard treatment for 10 days, followed by 56 days of follow-up. The primary outcome is the cure rate of pneumonia, and the secondary outcomes includes conversion rate of severe pneumonia, lower respiratory tract bacterial clearance, lactic acid (LC) clearance rate, temperature, C-reactive protein (CRP), criticality score (SMART-COP score), acute physiological and chronic health assessment system (APACHEII score) and clinical endpoint events. Adverse events will be monitored throughout the trial. Data will be analyzed according to a pre-defined statistical analysis plan. This research will disclose the efficacy of YHPG in acquired drug-resistant pneumonia. Ethics Statement and Clinical Trial Registration The research has been approved by the Research Ethics Committee of Hangzhou First People's Hospital (IRB#2021-20210408-01). Written informed consent from patients is required. This trial is registered with the Chinese Clinical Trials Registry (ChiCTR2100047501). Our results will be disseminated to the public through peer-reviewed journals, academic conferences and the Internet.